PERLINDUNGAN TERHADAP KONSUMEN GARAM YANG TIDAK BERYODIUM DI KABUPATEN LIMA PULUH KOTA - Adelina, Cindi; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 8 paragraph (1) Letter (a) and (e) of the Consumer Protection Act stipulates that businessactors are prohibited from producing and / or trading services that: (a) do not fulfill or do not comply withthe requirements and statutory provisions . Letter (e) states that it is not in accordance with the quality,level, composition, processing, style, mode or certain usage as stated in the label or description of the goodsand / or services. In the Lima Puluh Kota district there are business people who produce non-iodized salt sothat it harms consumers both materially and immaterial. The purpose of this thesis, namely: first to find outhow the implementation of consumer protection by businesses against the sale of non-iodized salt in LimaPuluh Kota District, secondly to find out why businesses do not produce iodized salt in Lima Puluh KotaRegency.This type of research casn be classified in sociological research. To obtain data in writing thisthesis, field research and library research were conducted. this research was conducted in Lima Puluh KotaRegency. while the population and sample are all parties related to the problems examined in this study,data sources used primary data and secondary data, data collection techniques in this study by observation,interviews, questionnaires, and literature studies.Based on the results of the problem research there are two points that can be concluded, the first isthat the implementation of consumer protection against the sale of non-iodized salt based on the reality inthe field is not as appropriate, as regulated in Law Number 8 of 1999 concerning Consumer Protectionbusiness actors are not responsible for producing or distributing non-iodized salt. Second, the reason saltproducers do not produce iodized salt because of several factors, namely economic / capital factors,education / knowledge factors and licensing factors. This happened due to lack of understanding of theproducers regarding rights and obligations as a producer.Keywords: Protection - Consumers - Non-iodized Salt